The minute virus of mice P39 transcription unit can encode both capsid proteins. - Labieniec-Pintel, L (1986)
The right-hand 80% of the genome of minute virus of mice (MVM) was cloned into the bovine papillomavirus type I shuttle vector and used to transfect mouse C127 cells. Transformed lines were isolated that efficiently produce both authentic MVM capsid proteins at a ratio similar to that seen in a normal viral infection, and these proteins assemble into intact empty virions. The only transcription of MVM sequences detected in these lines was representative of the viral P39 transcription unit, which therefore contains sufficient information to encode both authentic capsid proteins at the same regulated ratio seen in an infected cell.